The Effect of Giving Fe Tablets In Increasing Hb Level For Adolescents At Age 15-18 Years Old In Senior High School 3 Lahat 2019 - Eka Haryanti; Kamesyworo Kamesyworo (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study aims to determine the effect of giving Fe Tablets in increasing Hb levels in adolescents aged 15-18 years at Senior High School 3 (SMAN 3 ) of Lahat. This type of research is quantitative with the design of Quasy Experiment One Group Pretest Postest. Samples were taken using purposive sampling as many as 46 respondents. The measuring instrument used is the Hb meter. The results showed that before giving Fe tablets, it was found that of 46 respondents, 11 respondents (24%) had anemia. In the measurement after giving Fe tablets from 46 respondents there were 5 respondents (10.9%) having anemia. Test Dependent Test showed significant results (p = 0.001). This shows that there is an effect of giving Fe tablets in increasing Hb levels in adolescents aged 15-18 years